Designing of Potential Polyvalent Vaccine Model for Respiratory Syncytial Virus by System Level Immunoinformatics Approaches. (28th May 2021) - Naqvi, Syeda Tahira Qousain; Yasmeen, Mamoona; Ismail, Mehreen; Muhammad, Syed Aun; Nawazish-i-Husain, Syed; Ali, Amjad; Munir, Fahad; Zhang, QiYu
Abstract : Background . Respiratory syncytial virus (RSV) infection is a public health epidemic, leading to around 3 million hospitalization and about 66, 000 deaths each year. It is a life-threatening condition exclusive to children with no effective treatment. Methods . In this study, we used system-level and vaccinomics approaches to design a polyvalent vaccine for RSV, which could stimulate the immune components of the host to manage this infection. Our framework involves data accession, antigenicity and subcellular localization analysis, T cell epitope prediction, proteasomal and conservancy evaluation, host-pathogen-protein interactions, pathway studies, and in silico binding affinity analysis. Results . We found glycoprotein (G), fusion protein (F), and small hydrophobic protein (SH) of RSV as potential vaccine candidates. Of these proteins (G, F, and SH), we found 9 epitopes for multiple alleles of MHC classes I and II bear significant binding affinity. These potential epitopes were linked to form a polyvalent construct using AAY, GPGPG linkers, and cholera toxin B adjuvant at N-terminal with a 23.9 kDa molecular weight of 224 amino acid residues. The final construct was a stable, immunogenic, and nonallergenic protein containing cleavage sites, TAP transport efficiency, posttranslation shifts, and CTL epitopes. The molecular docking indicated the optimum binding affinity of RSV polyvalent construct with MHC molecules (-12.49 and -10.48 kcal/mol for MHC classes I and II, respectively). This interaction showed that a polyvalent construct could manage and control this disease. Conclusion . Our vaccinomics and system-level investigation could be appropriate to trigger the host immune system to prevent RSV infection.